Crystal c-axes (fabric analyser G50) of ice core samples (vertical thin sections) collected from the polar ice core RECAP, 115-534 m depth - Ilka Weikusat; Lara Gebhardt; Daniela Jansen; Nicolas Stoll; Sepp Kipfstuhl (PANGAEA, 2025)
Fabric Analyser data was obtained from 102 vertical thin sections (ca. 7 x 9 cm) of the REnland ice CAP project (RECAP) ice core to analyze the microstructural evolution and internal deformation with depth. Vertical ice thin sections were prepared and measured with the Fabric Analyzer G50 (resolution: 20 μm/pixel) in the field and at the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research. 55 cm long samples (bags) were cut into six thin sections and measurements were later background corrected and processed with the program cAxes. The stated depth (in m) of the section describes the sections extquotesingle or bags extquotesingle top. The derived data for sections is the mean grain size (mm^2) and its standard deviation (sigma), the grain size (mm^2) of the 50 largest grains, the grain size of the 25% largest grains (mm^2), grain size (mm^2) of the largest grains covering 95% of the sample area , the mean distance to length ratio (dtlr) and its standard deviation (sigma), the woodcock parameter, three eigenvalues (e1, e2, e3), and the Regelungsgrad. For bags, standard deviations and the aspect ratio and its standard deviation (sigma) is provided.